Insights into discrepancies in professional identities and role models in undergraduate medical education in the context of affective burden - Erschens, Rebecca; Skrypski, Isabelle; Festl-Wietek, Teresa; Herrmann-Werner, Anne; Adam, Sophia Helen; Schröpel, Carla; Nikendei, Christoph; Zipfel, Stephan; Junne, Florian (Frontiers in Psychiatry, 2024)
International evidence strongly suggests that medical students are at high risk of mental health problems. This distress, which can be mediated by a variety of individual, interpersonal and contextual factors within the curriculum, can be mitigated by effective coping strategies and diverse interventions.A central part of this discourse is the recognition that challenges of professional identity formation may contribute significantly to medical student distress. The focus of our study, therefore, is to examine discrepancies in professional identities and role models in undergraduate medical education in the context of affective burden. A cross-sectional survey was conducted among medical students at different stages of university education and high school graduates who intend to study medicine. The study employed Osgood and Hofstätter's polarity profile to evaluate the self-image of participants, the image of an ideal and real physician, and their correlation with depression and anxiety. Out of the 1535 students recruited, 1169 (76.2%) participated in the study. The students rated their self-image as somewhere between a more negative real image of physicians and a more positive ideal image. Medical students at all training levels consistently rated the ideal image as remaining constant. Significant correlations were found between the professional role models of medical students and affective symptoms, particularly for the discrepancy between the ideal image of a physician and their self-image.Furthermore, 17% and nearly 15% reported significant symptoms of depression and anxiety, respectively. Our study adds to the increasing body of knowledge on professional identity formation in medicine and socialisation in the medical environment. The study highlights the importance of discrepancies between self-image and ideal image in the experience of depressive and anxiety symptoms. Primary prevention-oriented approaches should incorporate these findings to promote reflective competence in relation to professional role models and strengthen the resilience of upcoming physicians in medical training.